Evaluation of The Tangerang Smart Program at State Junior High School 17 Tangerang in 2022 - Neneng Sri Rahayu; Aini Timur; Marlinda Erfanti; Reza Pirgianta (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
This study aims to provide input and evaluate the implementation of the Smart Tangerang Program, which offers tuition assistance to underprivileged students in Tangerang City. To reduce the number of school dropouts and prevent vulnerable children from discontinuing their education, the government has an obligation to provide free and quality education for all citizens, as mandated by the constitution. Consequently, the Tangerang City Government initiated the Smart Tangerang Program to enhance educational access for the less fortunate. However, previous studies have indicated challenges in implementing similar programs in other regions. Therefore, this research was conducted to find solutions and enhance the effectiveness of the Smart Tangerang Program. The Evaluation Model Countenance Stake, which encompasses three stages in an education program—context/planning, process/implementation, and outcome/output—was employed in this study. Data were collected through interviews with stakeholders involved in the Smart Tangerang Program's implementation, with the study's focus on SMP Negeri 17 Kota Tangerang. The research results are anticipated to provide valuable input and evaluation for refining the program further.